Uncommons in the commons : community initiated forest resource management - Ghate, Rucha S. (Rucha Suresh), 1961-; Chaturvedi, Alka. (New Delhi : Concept Pub. Co., 2004)
Case studies of five villages with reference to Chandrapur District and Gadhiroli District of the state of Maharastra, India.
Includes bibliographical references (p. [185]-200) and index.
Keywords: Community forests -- India -- Management; Forest management -- India -- Citizen participation